Real‐life experience of a lidocaine/tetracaine self‐occluding topical anesthetic for dermatological procedures. (12th November 2021) - Jimenez‐Cauhe, Juan; Boixeda, Pablo; Cornejo, Paloma; Fernandez, Sergio; Vitale, Maria; Serra, Carlos
Abstract: Background: Pliaglis ® is a self‐occluding topical anesthetic containing a eutectic mixture of 7% lidocaine and 7% tetracaine, with proven efficacy and safety in several trials. Aims: To evaluate the effectiveness and safety of Pliaglis ® for different dermatological procedures in real‐life clinical practice. Methods: This retrospective, multicenter study included 35 patients treated with Pliaglis ® prior to five dermatological procedures (pulsed dyed laser, picosecond laser, non‐ablative fractional laser, radiofrequency microneedling, and photodynamic therapy). The primary endpoint was to assess the pain during the procedure with a visual analogue score (VAS) from 0 (no pain) to 10 (most severe pain). Secondary endpoints were the global effectiveness and tolerability (from 0 = very low to 10 = excellent), and the adverse events (AEs) after Pliaglis ® removal, classified according to intensity (1–3). Results: The median and mean pain VAS reported by patients was 2 (range 0–9) and 2.9 (±2.3), respectively. More than 65% of the patients had a VAS score ≤3. The effectiveness reported by investigators was "very good" (median 8 [range 2–10], mean 7.5 [±1.9]), which was strongly correlated with the pain VAS reported by patients (Spearman coefficient = ‐ 0.9; p < 0.001). Forty‐five percent of patients reported AEs and they were transient and mostly mild, with a mean intensity score of 1.5 (range 1–3). Tolerability of Pliaglis ® was reported by investigators as "excellent" (median 10 [range 1–10], mean 9 [±1.8]). Conclusions: Pliaglis ® is an effective topical anesthetic for several dermatological procedures, with an excellent safety and tolerability profile.